TMEM63C, a Potential Novel Target for Albuminuria Development, Is Regulated by MicroRNA-564 and Transforming Growth Factor beta in Human Renal Cells - Miriam Orphal; Allan Gillespie; Karen Böhme; Jana Subrova; Andreas Eisenreich; Reinhold Kreutz (Karger Publishers, 2020)
Introduction: Transmembrane protein (TMEM) 63C is a member of the TMEM gene family and was recently linked to glomerular filtration barrier function and albuminuria. Its molecular function and expression regulation are largely unknown. Objective: In this study, we set out to characterize the regulating impact of microRNAs (miRNAs) such as miRNA-564 (miR-564) on TMEM63C expression in renal cells. Also, we examined the influence of transforming growth factor beta (TGF-ß) on TMEM63C expression and the potential impact of TMEM63C inhibition on epithelial-mesenchymal transition (EMT) in renal cells and on cell viability in human embryonic kidney 293 cells (HEK 293). Methods: Expression analyses were done using real-time PCR and Western blot. Dual luciferase assay was performed to determine the miRNA-mediated expression control. Cell viability was assessed via trypan blue exclusion staining. Results and Conclusions: MiR-564 reduced TMEM63C expression in HEK 293 and human podocytes (hPC). The treatment of renal cells with TGF-ß led to an increased expression of TMEM63C. Moreover, a reduced TMEM63C expression was associated with a changed ratio of EMT marker proteins such as α-smooth muscle actin versus E-cadherin in HEK 293 and decreased nephrin expression in hPC. In addition, cell viability was reduced upon inhibition of TMEM63C expression in HEK 293. This study demonstrates first mechanisms involved in TMEM63C expression regulation and a link to EMT in renal cells.